History and perspectives on Spanish literary journalism during the XXth century - Torregrosa Carmona, Juan-Francisco; Gaona Pisonero, Carmen (Historia y Comunicación Social, 2014)
This paper deals with a plot of Communication in History, which is called literary journalism in the twentieth century. In this field there is not only the legacy of the Anglo-Saxon authors but also in Spain has been relevant samples.
Keywords: Journalism; Literature; Spanish Newspapers; Twentieth century